PENGLIHATAN ANAK DAN EFEKTIVITAS VITAMIN A - Ronald Tandarto; Ferry Doringin; Zakaria Efendi (Jurnal Mata Optik, 2020)
Vitamin A deficiency in chindren can cause night blindness, even total blidness. However, the effect of vitamin A deficiency is not limited on th both sight problems. Thus, the author will describe the importance of vitamin A to five senses of children. As quoted in the book Blomhoff R, in his book Review of Retinoid Metabolism and Function 'Vitamin A plays a role in the formation of the sense of sight for humans', therefore the participation of parents and health workers supported by the government can prevent the impact that occurs if vitamin A deficiency occurs in children's vision.